Max headroom: Making time and space for Welsh manufacturing SMEs to flourish - David Pickernell; Nick Rich; Gareth Huw Davies; Annette Roberts; Pouya Sarvghad Moghadam; Gary Walpole; Alan Price (Welsh Economic Review (WER), 2024)
The Welsh manufacturing sector has undergone significant change over the last decade, with new technologies, greater promotion of the circular economy by policymakers, and a competitive environment affected by Brexit, covid and energy price rises, all impacting the business landscape. Consequently, Welsh manufacturing businesses, the vast majority of which are micro, small, or medium-sized enterprises, face issues concerning supply chains, training and skills, innovation, finance, infrastructure, and sustainability. This report summarises a recent study conducted by Swansea University, on behalf of the Federation of Small Businesses (Pickernell et al 2023). The research investigated the issues faced by Welsh small and medium-sized enterprises (SMEs), and identified short-term problems with energy and infrastructure, and difficulties recruiting sufficient qualified staff, as well as a lack of Welsh-based suppliers for many of the resources Welsh SMEs required. The research also highlighted the gap between short-term pressures and long-term vision, but that bridging that gap would allow Welsh manufacturing businesses to place themselves on a more resilient footing, build skills and employment and prepare for future opportunities.
Keywords: 330